A meaningful workplace: Framework, space and context - Steenkamp, Petrus L. (HTS teologiese studies, 2013)
An attempt was made to describe and to eventually implement work space that can be defined as psychologically meaningful and which has increased during the past 5−10 years. Indications are that various researchers on different continents have embarked on a journey to describe the meaningful workplace. Such a workplace is more than a geographical location, it is psychological space; space where the individual employee performs tasks that construe his or her work role, in collaboration with other individuals, within a framework of predetermined time frames, according to certain procedures, based on identified needs and within a formal workflow structure that is normally referred to as the organisation. Within this framework employees become alienated as a result of which the organisation as well as the individual suffer. The organisation experiences a loss of productivity, quality, innovation, et cetera, and the employee a loss of meaning in life and work. Yet, the workplace remains the space where meaning can be gained. It is both the framework and context for meaningfulness at work. Within this framework certain factors and constitutive elements play a facilitating role in experiencing meaningfulness. Various factors including values, and imbedded therein, the Protestant Ethic (PE), (and various other factors, such as for instance spirituality, culture, leadership and management style, etc.), play an important role as facilitating factors towards the experience of meaningfulness at work. Developing a framework and context, on a conceptual level for the positioning of these factors as contributories towards the meaningful workplace, is a first priority. This is what this article is about: to conceptualise the workplace as psychological space, framework and context for understanding the contributory role of PE (and other factors) towards the experience of meaningfulness at work. The positioning of values and the PE as Max Weber understood the concept will be presented in a follow-on article.